2012
DOI: 10.1163/157075611x616905
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the hepatic and renal structure and function after a growth promoter boldenone injection in rabbits

Abstract: Boldenone is an androgenic steroid that improves the growth and food conversion in food producing animals. In most countries worldwide, this anabolic steroid is forbidden for meat production. Recently, it is used by bodybuilders in both off-season and pre-contest, where it is well known for increasing vascularity while preparing for a bodybuilding contest. Therefore, our study was designed to investigate the possible effect of using growth promoter boldenone undecylenate on the rabbit liver and kidney … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 31 publications
(21 reference statements)
8
13
0
Order By: Relevance
“…Our results are in agreement with previous studies (El-Moghazy et al, 2012;Tousson et al, 2013). Moreover, similar results were recorded on AAS abuse (Urhausen et al, 2003).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our results are in agreement with previous studies (El-Moghazy et al, 2012;Tousson et al, 2013). Moreover, similar results were recorded on AAS abuse (Urhausen et al, 2003).…”
Section: Discussionsupporting
confidence: 94%
“…The histopathological examination of liver of BOL group revealed coagulative necrosis with lymphocytic infiltration, congestion of hepatic blood vessels, hydropic degeneration and vacuolations of hepatocytes, as well as activation of apoptosis and numerous apoptotic bodies throughout the hepatic parenchyma. These findings are in agreement with those of El-Moghazy et al (2012) who reported that intramuscular injection of BOL to rabbits has a marked adverse effect on hepatic structure. Similar changes in hepatic tissue of cattle have been reported by Groot and Biolatti (2004).…”
Section: Discussionsupporting
confidence: 93%
“…The results of the present study revealed marked oxidative stress in testis and kidney tissues after Bol injection compared to normal control. This is consistent with the previous studies who reported that, the anabolic androgenic steroids induced oxidative stress as indicated by elevation of serum MDA level and alterations in the liver and kidney antioxidant defense systems (21,22). The oxidative stress induced by boldenone injection could explain the increased DNA fragmentation as compared to control group.…”
Section: Discussionsupporting
confidence: 92%
“…Anabolic-androgenic steroids are defined as synthetic derivatives of the endogenous sex hormone testosterone that plays a key role in the development of male reproductive tissue (such as the testis and prostate) as well as in puberty, sexual behavior, spermatogenesis and plays promoting secondary sexual characteristics such as increased muscle, bone mass and hair growth (Mitchell et al, 2009;Balthazart, Ball, 2010;Mohammed et al, 2016). Anabolic steroids are forbidden for meat production and human use in KAS, and most countries worldwide due to their undesirable effects included blood and cardiovascular disorders (Santos et al, 2006;Tousson et al, 2016;Waljee et al, 2016), liver dysfunction (Van Amsterdam et al, 2010;Barakat et al, 2015), kidney disease (Barakat et al, 2015), tendon damage (Battista, Combs, Warne, 2003), testicular problems (Tousson et al, 2012;El-Masry et al, 2017), psychiatric and behavioural disorders in both sexes (Salas-Ramirez, Montalto, Sisk, 2010), as well as other problems on the human body (Saleh, Waded, 2014).…”
Section: Introductionmentioning
confidence: 99%